The Palm Fringed Coast, Trinidad, B.W.I. - (:unkn) unknown (Queen's Park Hotel Co. Ltd.,[Trinidad and Tobago], 2011)
The postcard shows coconut palms along the coast in Trinidad. Postcard number 13.
Colour: Sepia; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Coasts--Trinidad and Tobago; Trees--Trinidad and Tobago; [1930]; Coconut palm--Trinidad and Tobago; Seas--Trinidad and Tobago; Bodies of water--Trinidad and Tobago